Role of Intact Cytoskeleton Organization in Nuclear Import and Speckle Formation of Phytochrome A and B in Arabidopsis Seedlings - Panigrahy1*, Madhusmita (Journal of Phytology, 2011)
Phytochromes are the primary photoreceptors for red and far-red light in plants and control various aspects of photomorphogenesis. Phytochomes are encoded by five genes (phytochrome A to E) in Arabidopsis.Ã‚Â Phytochromes have been shown to be transported to the nucleus upon light irradiation and can form a speckled pattern. Nuclear import is the most essential step for the phytochromes to initiate specific photo-sensory transduction pathways. Number and size of these nuclear speckled structures (speckles) have been functionally correlated with the light-responsiveness. In the current study, the role of intact cytoskeleton in nuclear import process and subsequent speckle formation of phytochrome A (phyA) and phytochrome B (phyB) GFP fusion proteins was studied in Arabidopsis seedlings. The studies were carried out in three different physiological conditions, where the intact cytoskeleton of the cell is either reorganized or disrupted. These conditions are (i) at lower temperature, where overall cytoskeleton dynamics is altered, (ii) in the protoplasts where tubulin organization is altered and (iii) the application of cytochalasin B, an actin cytoskeleton disrupting drug. The disappearance of the pre-formed speckles in these experimental conditions was also investigated. Here we conclude that the nuclear import kinetics of phyA and B is slower but could not be abolished in all these conditions tested.Ã‚Â Moreover, formation and disappearance of speckles from the nucleus is found to be delayed but not completely abolished when the cytoskeleton is disrupted.Ã‚Â These result suggest that phytochrome nuclear import, dynamics of nuclear speckles are partly contributed by cytoskeleton components and partly by other protein-macromolecular interaction. Key words: Phytochrome, Arabidopsis thaliana, Cytoskeleton, Speckle formation, Nuclear bodies, Nuclear transport, Cytochalasin B Abbreviation: phy, Phytochrome; R, Red; FR, Far-red; RT, Room temperature; cytB, Cytochalasin B <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Madhusmita Panigrahy. Role of Intact Cytoskeleton Organization in Nuclear Import and Speckle Formation of Phytochrome A and B in Arabidopsis Seedlings. J Phytol 3/1 (2011) 59-67